Pemberdayaan Keluarga tentang Kemandirian Lansia dalam Pemenuhan Aktivitas Sehari-Hari di Posyandu Lansia Rindang Benua Wilayah Kerja Puskesmas Pahandut Palangka Raya - Berthiana Berthiana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Elderly residents need to be given attention because usually, at old age, there will be many complaints/health problems due to decreased organ function. Therefore it needs various supports from various parties, especially families, in increasing the independence of the elderly in fulfilling daily activities so that the elderly can maintain their health as optimal as possible. The results showed that increased knowledge about good family support and awareness of the elderly in doing their own independent activities would improve the quality of life of the elderly in their old age. There are two evaluations carried out in this community service: pre-test and post-test evaluation. For the pre-test results of 30 participants, 45% are good, and 55% are not good after the activity process is carried out; the post-test gets 90% good and 10% less good. The conclusion from the implementation of community service participants in community service activities can understand and understand the role of the family regarding the independence of the elderly in fulfilling daily activities